1987
DOI: 10.1002/jcp.1041330202
|View full text |Cite
|
Sign up to set email alerts
|

Insulin and α2‐macroglobulin‐methylamine undergo endocytosis by different mechanisms in rat adipocytes: I. Comparison of cell surface events

Abstract: This ultrastructural study compared the endocytosis of a peptide hormone, ferritin-labeled insulin (Fm-I) or gold-labeled insulin (Au-I), and a non-hormonal ligand, gold-labeled alpha-2-macroglobulin-methylamine (Au-alpha 2MGMA), by rat adipocytes. Quantitative analysis of the cell surface showed that coated pits occupied 0.4% of the adipocyte surface. This was one fifth to one tenth of that which has been reported on fibroblasts and hepatocytes, cell types in which receptor-mediated endocytosis has been exten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
34
1

Year Published

1987
1987
2007
2007

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 77 publications
(38 citation statements)
references
References 31 publications
3
34
1
Order By: Relevance
“…Fyn) interact directly with caveolin, and the kinase domains of nonreceptor tyrosine kinases and receptor tyrosine kinase are extremely homologous (11,32,33). (ii) Four receptor tyrosine kinases (EGF-R, PDGF-R, insulin-R, and nerve growth factor receptor (trk)) have now been shown to co-purify with caveolae or caveolae-like membrane domains (16,17,20,25,34), suggesting that a structural property that is common to this protein family directs caveolar localization.…”
Section: Discussionmentioning
confidence: 99%
“…Fyn) interact directly with caveolin, and the kinase domains of nonreceptor tyrosine kinases and receptor tyrosine kinase are extremely homologous (11,32,33). (ii) Four receptor tyrosine kinases (EGF-R, PDGF-R, insulin-R, and nerve growth factor receptor (trk)) have now been shown to co-purify with caveolae or caveolae-like membrane domains (16,17,20,25,34), suggesting that a structural property that is common to this protein family directs caveolar localization.…”
Section: Discussionmentioning
confidence: 99%
“…Caveolae are morphologically induced during adipocyte differentiation (2). Ligand-bound insulin receptor localizes to adipocyte caveolae (27), and insulin stimulation leads to the rapid tyrosine phosphorylation of caveolin-1 in a time-and dose-dependent manner (26). In addition, in response to insulin stimulation, caveolin-1 rapidly associates with an unknown phosphoprotein of 30 kDa and an intracellular pool of caveolin-1 undergoes translocation to the plasma membrane (15,26).…”
Section: Methodsmentioning
confidence: 99%
“…25) Immunogold electron 17) and immuno‰uorescence microscopy 18) further demonstrated that IRs are highly concentrated in caveolae. Additionally, Couet et al, demonstrated the presence of a caveolin binding motif (qXqXXXXq: where q is aromatic amino acid) in the b-subunit of IRs that could bind to the scaŠold domain of caveolin.…”
Section: Insulin Signaling Via Caveolaementioning
confidence: 99%